2022
DOI: 10.3390/toxics10030133
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Uptake of Arsenic Induces Increased Toxicity with Cadmium at Non-Toxic Concentrations on Caenorhabditis elegans

Abstract: Cadmium (Cd) and arsenic (As) are widely distributed pollutants that co-exist in the environment; however, their joint toxicity on living organisms is still largely unknown. In this study, we explored the joint toxicity of concurrent exposure to Cd and different As species at low concentrations on Caenorhabditis elegans (C. elegans) in comparison to single exposures. Endpoints such as germ cell apoptosis, the number of oocytes, brood size, and the life span were employed to evaluate the combined effects of Cd … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 73 publications
0
5
0
Order By: Relevance
“…6 D); therefore it would be misleading to deem MTL-1 to be “zinc-specific”. However, we have also demonstrated that when both proteins are simultaneously present in vitro , Cd 2+ partitions overwhelmingly into MTL-2, leaving MTL-1 largely populated with Zn 2+ ( Pei et al, 2022 ), in full accordance with measured affinity constants: As previously stated, the average stability constant for Cd 7 MTL-1 (log K = 13.1) is almost two orders of magnitude lower than that of Cd 6 MTL-2 (log K = 15.0) (Hall et al). These considerations emphasise the important concept of relative affinities ( Foster and Robinson, 2011 ).…”
Section: Resultsmentioning
confidence: 77%
See 2 more Smart Citations
“…6 D); therefore it would be misleading to deem MTL-1 to be “zinc-specific”. However, we have also demonstrated that when both proteins are simultaneously present in vitro , Cd 2+ partitions overwhelmingly into MTL-2, leaving MTL-1 largely populated with Zn 2+ ( Pei et al, 2022 ), in full accordance with measured affinity constants: As previously stated, the average stability constant for Cd 7 MTL-1 (log K = 13.1) is almost two orders of magnitude lower than that of Cd 6 MTL-2 (log K = 15.0) (Hall et al). These considerations emphasise the important concept of relative affinities ( Foster and Robinson, 2011 ).…”
Section: Resultsmentioning
confidence: 77%
“…In contrast, LA-ICP-MS returned negligible background signal for the cadmium isotope 111 Cd and thus was applied to measure the accumulation of cadmium in individual worms. The zinc (150 μM) and cadmium (30 μM) doses chosen for this study are based on a previous publication ( Anderson et al, 2001 ) and reflect equi-toxicity, at least in terms of reproductive performance, a key lifecycle endpoint and sensitive indicator of metal toxicity ( Pei et al, 2022 ) and are within the concentrations found in natural environments. It should be noted that, prior to any quantification, the intestinal lumen was allowed to clear to ensure the removal of free-floating metals.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…found that cadmium and arsenic can synergistically lead to reproductive and developmental toxicity of C. elegans . 48 The interaction between cadmium and arsenic is related to physicochemical properties and toxic mechanisms. It was found that both cadmium and arsenic are positively charged ions, which have high affinity for electron-rich thiol and selenol residues in proteins, and can stably bind to them, affecting protein and enzyme activities.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, mutant SJ4058 [hsp-60::GFP + lin-15(+)] and CF1553 [(pAD76) sod-3p::GFP + rol-6(su1006)] provide valuable tools for investigating protein dynamics in vivo [40][41] . The Stress Resistance model of C. elegans can also be applied in the realm of environmental protection research, encompassing investigations on excessive heavy metal contamination, plastic pollution, soil and water pollution, among other elds [42][43][44] .…”
Section: Stress Resistancementioning
confidence: 99%